Paliperidone Extended-Release Tablets for the Treatment of Methamphetamine Use Disorder in Chinese Patients After Acute Treatment: A Randomized, Double-Blind, Placebo-Controlled Exploratory Study - Wang, Gang; Ma, Li; Liu, Xuebing; Yang, Xue; Zhang, Sheng; Yang, Yongde; Xu, Zaifeng; Hao, Wei (Frontiers in Psychiatry, 2019)
Background: To test paliperidone extended-release (ER) for efficacy in decreasing methamphetamine (METH) use and reducing psychotic symptoms in METH-dependent patients after detoxification. Rates of adverse events with paliperidone ER versus placebo were also compared. Methods: After discharge and seven days without medication, 80 treatment-seeking METH-dependent participants were randomly assigned to paliperidone ER (3 mg once daily; n=40) or placebo (once daily; n=40) for 84 days under double-blind conditions. The participants attended clinics weekly to provide urine samples that were analyzed for METH metabolites, to complete research assessments, and to receive substance use and medication counseling. Results: Fifty-six percent of follow-up visits and final visits were completed. The placebo group had a significantly lower retention (51.5 days, 95% CI, 41.6-61.4) than the paliperidone ER group (69.4 days, 95% CI, 61.9-76.9, p=0.016). Paliperidone ER was a protective factor against psychotic symptom relapse (hazard ratio (HR)=0.15, p=0.003). Moreover, there were statistically significant effects of paliperidone ER on psychosis severity and METH craving, assessed by mean changes in Positive and Negative Syndrome Scale (PANSS) total scores, Clinical Global Impression-Severity (CGI-S) scores and METH craving scores over time (p=0.006, p=0.002 and p=0.03 for the medication by time interaction effect, respectively). There were no statistically significant differences between the two groups on METH use. There were no serious adverse events related to the study drug. Conclusion: Compared with placebo, paliperidone ER administration resulted in a better retention rate and lower psychotic symptom relapse, but we did not find significantly reduced METH use among adults after acute METH detoxification treatment.